Analisis Deskriptif Penggunaan 「ータばかり」、「ータところ」、「ータとたん」 yang Menyatakan Beberapa Saat Waktu yang Sudah Berlalu Setelah Suatu Aktivitas Terjadi. - Muhlisian, Asep Achmad (Universitas Negeri Jakarta, 2013)
The research purpose to analize differences, function and objective meaning of synonym 「ータばかり」,「ータところ」and「ータとたん」which used to explain several times after oneactivity finished. The research used seven data object from Japanese dictionary whichexplained by descriptive method. The analysis explained that even the synonym have samemeaning, there are also differences which shows in sentence examples. The result shows thatthere are four differences among「ータばかり」,「ータところ」and「ータとたん」in thesentences. The differences are in function, time, particle used in sentence and nuance.